Can formalisation of pastoral land tenure overcome its paradoxes? Reflections from East Africa - Robinson, Lance W.; Flintan, Fiona E. (Springer, 2022)
Legal frameworks for communal land rights in Ethiopia, Kenya, and Tanzania are now gaining momentum. Questions can be raised as to whether, how, and to what extent these frameworks take into account the disadvantages of formalising tenure and the complexities of pastoral resources. In this paper, we consider the impact of these challenges on the formalisation of communal ownership, beginning with an overview of how commons theory has influenced land governance policies and how it is applied to pastoral systems. We identify the main challenges that land policy interventions in East Africa face and ways in which the conceptual models of shared property rights embodied in current land tenure regimes are not well adapted to the socio-ecological characteristics of some rangeland landscapes. We argue that policy interventions capable of overcoming the paradox of pastoral tenure and strengthening tenure security while addressing herders’ needs for mobility and flexibility will often involve the progressive recognition of layers of sometimes overlapping rights, rather than attempts to subdivide landscapes into simple mosaics of discrete communal territories. This paper is based on an analysis of the legal frameworks for land tenure in the three countries and a review of the literature on pastoralism and land governance in the region.